Leaders’ Expressed Humility and Followers’ Feedback Seeking: The Mediating Effects of Perceived Image Cost and Moderating Effects of Power Distance Orientation - Qian, Jing; Li, Xiaoyan; Song, Baihe; Wang, Bin; Wang, Menghan; Chang, Shumeng; Xiong, Yujiao (Frontiers in Psychology, 2018)
We developed and tested a model to identify the role of leaders’ expressed humility on employees’ feedback-seeking processes. The data used in our study was from a sample of 248 employees and 57 of their immediate supervisors. The results revealed that: 1) leader’s expressed humility positively related to employees’ feedback seeking mediated by employees’ perceived image cost; and 2) power distance orientation moderated the relationship between leader’s expressed humility and employees’ perceived image costs, such that the relationship was stronger when the power distance orientation was lower rather than higher. The results offer new insight into potential managerial practices that aim at stimulating feedback seeking. We conclude with a discussion for future research.